The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1089/jwh.2016.6098
|View full text |Cite
|
Sign up to set email alerts
|

Offering Prenatal Screening in the Age of Genomic Medicine: A Practical Guide

Abstract: As the spread of prenatal genetic screening continues, providers will increasingly need to update their practice to accommodate new screening modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Maintaining high levels of informed choice will be very dependent on effective training of health professionals to ensure they can provide up‐to‐date unbiased information and also have the confidence and skills to support parents to discuss prenatal testing options in a way that reflects their patients' values and beliefs. Recent guidelines emphasise the importance of having pretest face‐to‐face conversations with patients about their values regarding termination and pregnancy planning to help direct and personalise counselling as well as ensuring patients are clear that screening and testing are optional . Current research shows it is possible to achieve high levels of informed decision‐making for NIPT, but given the possibility of NIPT as a first line screening test continued research in this area is important.…”
Section: Resultsmentioning
confidence: 99%
“…Maintaining high levels of informed choice will be very dependent on effective training of health professionals to ensure they can provide up‐to‐date unbiased information and also have the confidence and skills to support parents to discuss prenatal testing options in a way that reflects their patients' values and beliefs. Recent guidelines emphasise the importance of having pretest face‐to‐face conversations with patients about their values regarding termination and pregnancy planning to help direct and personalise counselling as well as ensuring patients are clear that screening and testing are optional . Current research shows it is possible to achieve high levels of informed decision‐making for NIPT, but given the possibility of NIPT as a first line screening test continued research in this area is important.…”
Section: Resultsmentioning
confidence: 99%
“…This may lead people to make critical pregnancy decisions without undergoing prenatal diagnosis (103). HCPs are thus reluctant to use biased materials to counsel their patients (9). Moreover, some have expressed concern that even information provided by HCPs themselves is biased, as it focuses primarily on health risks associated with T21 and not on the positive lived experiences of families (103,139).…”
Section: The United Statesmentioning
confidence: 99%
“…Genetic counseling, when practiced ideally, is meant to provide expectant persons with accurate, up-todate, balanced information so that informed decisions could be made. Research from the United States and the Netherlands has demonstrated that sometimes expectant couples feel such counseling falls short-sometimes perceived as biased, incomplete, and outdated [14,15,19,20]. Future research will be necessary in order to understand the synergistic impact that all of these factors have on the overall number of live births with DS.…”
Section: Access To and Coverage Of Prenatal Diagnosis For Down Syndromementioning
confidence: 99%